Factors Associated with Mortality Among Stroke Patients Admitted to the Intensive Care Unit: A Retrospective Study - Andriani; Asri, Yuni; Maharani, Ananda Sagita (Pustaka Galeri Mandiri, 2026)
Stroke is a leading cause of mortality worldwide, particularly among patients requiring intensive care. Identifying factors associated with mortality in the intensive care unit (ICU) is essential to improve clinical management. This study examined factors associated with mortality among stroke patients admitted to the ICU. A retrospective analytic study was conducted using secondary medical record data of stroke patients admitted to the ICU of TK. II R.W. Mongisidi Hospital, Manado, Indonesia, between December 2025 and January 2026. A total of 55 patients were included. Mortality during ICU stay was the primary outcome. Sociodemographic variables, clinical factors, and length of stay were analyzed using Chi-square and Fisher’s exact tests in SPSS version 26, with significance set at p < 0.05. The mortality rate was 41.8%. Most patients had a history of hypertension (78.2%) and uncontrolled blood pressure (87.3%). Age, gender, education, employment status, marital status, genetic factors, medication adherence, history of hypertension, and blood pressure status were not significantly associated with mortality (p > 0.05). Length of ICU stay was significantly associated with mortality (p < 0.001), with deaths occurring more frequently among patients with shorter stays. Length of ICU stay was the only factor significantly associated with mortality among ICU-admitted stroke patients